2017
DOI: 10.5114/wiitm.2017.67207
|View full text |Cite
|
Sign up to set email alerts
|

A prospective 4-year study of insulin resistance and adipokines in morbidly obese diabetic and non-diabetic patients after gastric banding.

Abstract: IntroductionThere are insufficient data regarding the changes in adipokine levels after laparoscopic adjustable gastric banding (LAGB) in diabetic and non-diabetic patients and their effects on insulin resistance and type 2 diabetes remission.AimTo assess leptin, adiponectin, and insulin resistance changes after LAGB in diabetic and non-diabetic morbidly obese patients.Material and methodsOne hundred and three patients (37 with and 66 without type 2 diabetes) underwent LAGB from January 2009 to January 2010. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…We found that the reductions in LAR were driven primarily by an increase in adiponectin rather than a reduction in leptin, and these changes were proportional to the reduction in weight after surgery, consistent with the Unamuno study. The changes we observed in leptin and adiponectin concentrations were less than those described after bypass bariatric surgery 3,6,7 and are more consistent with those previously described after banding 8 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that the reductions in LAR were driven primarily by an increase in adiponectin rather than a reduction in leptin, and these changes were proportional to the reduction in weight after surgery, consistent with the Unamuno study. The changes we observed in leptin and adiponectin concentrations were less than those described after bypass bariatric surgery 3,6,7 and are more consistent with those previously described after banding 8 .…”
Section: Discussionsupporting
confidence: 90%
“…A key limitation of our study is its modest size (reflected in the borderline statistical significance of the reduction in LAR, for example), but the effects of bariatric surgery on metabolic outcomes and cardiovascular disease risk tend to be so profound that even in randomised controlled trials, surgical interventions require population sizes 2 that are orders of magnitude smaller than those in drug 26 or lifestyle intervention trials 27 . Our cohort size is similar to other surgical studies 3 , 6 8 , 15 and our findings around the correlation between weight loss and reduced LAR are statistically robust. Rather than using LAR as the only index of insulin sensitivity, future studies could also examine indices related to fasting glucose and insulin (such as the homeostasis model assessment, HOMA 28 ), in order to strengthen causal inference on the impact of bariatric interventions on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations